A comparative study of the antimicrobial properties and antioxidant enzyme activities of field-grown and in vitro- propagated plants of endemic Digitalis trojana Ivanina - Çördük, Nurşen; Demirbas, Sefer; Hacıoglu Dogru, Nurcihan (Archives of Biological Sciences, 2017)
The antimicrobial properties and antioxidant enzyme activities of field-grown and in vitro-propagated plants of Digitalis trojana Ivanina (Helen of Troy foxglove), a perennial endemic plant species of Turkey, were compared. The field work was carried out in May and July 2014, and plant samples of D. trojana were collected from Kazdağı (Turkey). Propagation of D. trojana was achieved by culturing leaf explants on MS medium supplemented with 13.3 µM 6-benzylaminopurine (BA) and 0.53 µM α-naphthaleneacetic acid (NAA). The antimicrobial activity, plant lipid peroxidation levels and antioxidant enzyme (superoxide dismutase (SOD), catalase (CAT), peroxidase (POX), ascorbate peroxidase (APX), glutathione reductase (GR)) activities were analyzed in 12- and 17-week-old in vitro-grown Digitalis plants collected in May and July from two different localities at 430 and 1173 m above sea level. Although the in vitro-propagated plants had very low antagonistic activities compared to field-grown plants, they exhibited remarkably similar antibacterial activities against Escherichia coli ATCC 11230, Pseudomonas aeruginosa ATCC 27853 and Bacillus subtilis ATCC 6633. There were no important differences between plants collected from the two localities (430 and 1173 m a.s.l.). Biochemical analysis showed that the antioxidant enzyme (SOD, APX, GR) activities of field-grown plants were higher than in vitro-grown plants. Also, the difference in altitude at which the plants were grown was apparently linked to decreases in antioxidant enzyme activities, except for POX in field-grown plants collected in July. https://doi.org/10.2298/ABS161216004C Received: December 16; 2016; Revised: January 6, 2017; Accepted: February 2, 2017; Published online: March 10, 2017 How to cite this article: Corduk N, Demirbas S, Hacioglu Dogru N. A comparative study of the antimicrobial properties and antioxidant enzyme activities of field-grown and in vitro- propagated plants of endemic Digitalis trojana Ivanina. Arch Biol Sci. 2017;69(4):603-10.